2022
DOI: 10.1002/ase.2207
|View full text |Cite
|
Sign up to set email alerts
|

Flipped anatomy classroom integrating multimodal digital resources shows positive influence upon students' experience and learning performance

Abstract: Anatomy is shifting toward a greater focus on adopting digital delivery. To advance digital and authentic learning in anatomy, a flipped classroom model integrating multimodal digital resources and a multimedia group assignment was designed and implemented for first‐year neuroanatomy and third‐year regional anatomy curricula. A five‐point Likert scale learning and teaching survey was conducted for a total of 145 undergraduate health science students to evaluate students' perception of the flipped classroom mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 74 publications
1
41
1
2
Order By: Relevance
“…In addition, proficiency in surgical care is complex as it not only involves the knowledge of instrumentation procedures but also a comprehensive knowledge integration for the organ being operated. In this context, digital resources could provide sophisticated tools pertinent to pre‐operative studies (Xiao & Adnan, 2022). Overall, future anatomy ecosystems may incorporate physical and/or digital cadavers, particular in the field of medical and surgical training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, proficiency in surgical care is complex as it not only involves the knowledge of instrumentation procedures but also a comprehensive knowledge integration for the organ being operated. In this context, digital resources could provide sophisticated tools pertinent to pre‐operative studies (Xiao & Adnan, 2022). Overall, future anatomy ecosystems may incorporate physical and/or digital cadavers, particular in the field of medical and surgical training.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of literature support the notions that digital technologies enhance anatomical education across multiple health disciplines (Pringle & Paul, 2018). Digital approaches are being combined with the blended learning for lectures and practical applied classes (Xiao & Adnan, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a fully online anatomy course cannot ensure students' achievement of necessary learning outcomes (Tg Muda et al, 2021). The adoption of blended learning and the implementation of innovative pedagogical ideas during the pandemic have suggested efficient methods to combine traditional face‐to‐face teaching with online modalities (Abu Bakar et al, 2022; Xiao & Adnan, 2022). However, these approaches' effectiveness and implications for post‐pandemic anatomy curricula must be explored further to ensure their sustainability.…”
Section: Discussionmentioning
confidence: 99%
“…The Covid‐19 pandemic has diversified anatomists' thoughts on how to design future anatomy curricula during the pandemic's aftermath. Covid‐19‐related disruptions have shown that anatomy education has yet to become future‐ready and requires various stakeholders' e.g., involvement in improving the hybrid learning approach so that it is responsive and adaptable to future uncertainties (Xiau & Adnan, 2022). Continuous needs assessments and the re‐evaluation of the anatomy curricula are also needed to establish a basis for curricular changes and redevelopment (Mishall et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Such an approach needs to balance intuitive technological solutions that effectively connect students to relevant and supporting resources without losing teacher interaction and peer support. Anatomy teaching can be delivered via a careful combination of asynchronous and synchronous delivery, a spatially and temporally hybrid teaching model feasible for gross and microscopic anatomy teaching (Caruso, 2021 ; Xiao & Adnan, 2022 ). The asynchronous activities are applied to enable students to learn at times and in locations most convenient for them, while the synchronous sessions maintain a structure that focuses on interaction and collaboration in a real‐time manner (online or face‐to‐face).…”
Section: Future Outlooksmentioning
confidence: 99%